Elemental composition of particulate matters around Urmia Lake, Iran. Issue 1 (2nd January 2017) - Gholampour, Akbar; Nabizadeh, Ramin; Hassanvand, Mohammad Sadegh; Nazmara, Shahrokh; Mahvi, Amir Hossein
ABSTRACT: Atmospheric particulate matters and their elements were concurrently measured at two sites located in the north and southeast parts of Urmia Lake from January to September 2013. At both sampling sites, average concentrations of total suspended particulate, particles with the aerodynamic diameter of smaller than 10 µm, smaller than 2.5 µm, and smaller than 1 µm were 260 ± 106, 180 ± 73, 30 ± 8, and 25 ± 7 µg m −3, respectively. The analyzed water soluble ions accounted for approximately 11%–13% mass concentrations of total suspended particulate and 8%–9% of particles smaller than 10 µm, and the sum of the concentrations of the analyzed elements associated with both ranged from 9 to 41 µg m − 3 (6.5%–9.6% in mass) and 7 to 26 µg m − 3 (5.5%–11.3% in mass), respectively. Thus, particulate matter was composed of a complex mixture of minerals such as halite, quartz, gypsum, hexahydrite, and Bassanite.